Health law, Brexit and medical devices: A question of legal regulation and patient safety. (June 2018) - McHale, Jean V.
Brexit is already posing many major challenges for those concerned with health and social care. This article explores one area, that of the regulation of medical devices which has been fundamentally underpinned by EU law and asks what Brexit means for future regulation in the United Kingdom. This article begins by outlining the importance of ensuring standards of quality and safety for medical devices and the consequences if things go wrong. The second section of the article outlines the current EU regulation of medical devices. It explores questions such as the role of the notified bodies, the problems of lack of central regulation and the role of vigilance processes. The third section explores the options for medical device regulation post Brexit in the light of the ongoing reform of the law in this area and the implementation of new EU Regulations. It considers the prospects for reciprocity and for alignment in the future. The article concludes by arguing that, while the new system for regulation of medical devices in the EU is not perfect, it nonetheless provides an important opportunity for restructuring device regulation and providing greater opportunities for facilitating safety. It is important to ensure that, as far as possible, we do not lose such an opportunity at domestic level post Brexit.